2011
DOI: 10.1016/j.jns.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The association between cigarette smoking and multiple sclerosis

Abstract: Genetic factors partially explain the susceptibility of multiple sclerosis (MS) and might even relate to the clinical course. Still, many epidemiological studies point at an important role for environmental factors in MS. Smoking is one of the major candidates. In this review we provide an overview of the epidemiological studies on cigarette smoking and the association on MS risk and MS clinical course. In addition, we discuss the possible biological pathways that may influence neurological damage in MS. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 92 publications
(122 reference statements)
0
25
0
1
Order By: Relevance
“…Cigarette smoking (CS) is a major risk factor for atherosclerotic vascular disease, Chronic Obstructive Pulmonary Disease (COPD), and cancer , and it affects the function of numerous other organs and systems . The effect of CS on hematopoietic stem/progenitor cells has been little explored.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking (CS) is a major risk factor for atherosclerotic vascular disease, Chronic Obstructive Pulmonary Disease (COPD), and cancer , and it affects the function of numerous other organs and systems . The effect of CS on hematopoietic stem/progenitor cells has been little explored.…”
Section: Introductionmentioning
confidence: 99%
“…Though there are some inconsistencies the accumulated epidemiological evidence points to tobacco smoke being correlated with increased susceptibility [2,[6][7][8][9][10], faster clinical progression [11][12][13][14][15][16][17] and increased mortality in patients with MS [18][19][20][21][22][23]. The pathological basis for this is currently unknown but there are some putative mechanisms.…”
Section: Pathological Basismentioning
confidence: 99%
“…Multiple retrospective and prospective studies since 1965, including case-control and cohort types, have shown increased susceptibility to MS [2,[6][7][8][9][10]. The reported average risk ratio (RR) varied between 1.4 and 1.8 and a recent meta-analysis by Handel et al calculated the RR as 1.48 (95% CI: 1.35-1.63; p < 10 -15 ) when conservatively limiting the analysis to ten studies where smoking behavior was described prior to disease onset and the nonconservative RR as 1.52, (95% CI: 1.39-1.66; p < 10 -19 ) [2].…”
Section: Smoking and Susceptibility To Msmentioning
confidence: 99%
“…The cause of MS is not known, but several factors have been shown to be associated with the risk of developing this disease including vitamins [1], smoking [2], genetic factors [3, 4], and infections [5]. A link between the first clinical attack or relapses in MS and infections has been proposed on the basis of epidemiological studies [6].…”
Section: Introductionmentioning
confidence: 99%